Hubungan Pendidikan, Akses Pelayanan Kesehatan dan Dukungan Keluarga dengan Pemanfaatan Pelayanan Kesehatan Penderita TB Paru BTA+ di Puskesmas Janti Kota Malang - Purbantari, Alfreda Dinayu; Roesdiyanto, Roesdiyanto; Ulfah, Nurnaningsih Herya (Preventia: The Indonesian Journal of Public Health, 2019)
Tuberculosis (TB) is a contagious disease that is still the world's attention, Until now, there is not a single country that is free of TB (Kemenkes 2011). Public Health Center (puskesmas) Janti is a puskesmas where the number of TB BTA+ sufferers increases every year while the number of treatment success rate at Puskesmas Janti decreases every year. In 2013 is 96%, in 2014 is 87,50% and in 2015 is 85,37%. Increasing the number of patients and decreasing the number of success rates of treatment indicates that the utilization of health services is less. This study aims to find out the relationship of Education, Health Service Access and Family Support with Health Service Utilization of BTA+ Pulmonary TB Patients at Public Health Center (puskesmas) Janti Malang. The design of this study is quantitative correlation with samples of all patients with TB Paru + BTA who are still doing treatment at Puskesmas Janti in September 2016 until April 2017. The analysis used correlation test and logistic regression test with cross sectional approach. The results of the research analysis found that there is a significant relationship between education, access to health services and family support together with the utilization of health services of patients Tb Paru BTA+. Based on the results of determination coefficient R2 (Nagelkerke) of 0.619, this means that education (X1), access to health services (X2), and family support (X3) has contributed 61.9% to the utilization of health services of patients with TB Paru BTA+ at Puskesmas Janti.